Measurement Instrument of Soft Skills and Work Ethics - Soelistiyowati, Endang; Yuanti, Erlin Estiana; Sari, Yohana Ika Harnita; ., Suwardo (Advances in Social Sciences Research Journal, 2020)
There has been an issue toward to what extent a formal education specifically embeds soft skills and work ethics, the aspects that employees must possess, and what efforts have been given to help develop them. This paper aims at developing a measurement instrument to assess, to help improve the employees’ level of soft skills and work ethics in industries and at the same time to give an insight about what universities should prepare to help their students acquire a sufficient acquisition of soft skills and work ethics. This research is a Research and Development (R&D), aimed at developing a measurement instrument on skills and work ethics. Partial Least Square (PLS) was employed to confirm the validity and reliability of the instrument. Some observations in industries were done, and semi-structured qualitative interviews and Focused Group Discussion (FGD) were conducted with stakeholders, HR managers, and psychologists. The results show that 47 out of 56 items are valid to measure intrapersonal, interpersonal skills, and communication skills. While for the work ethics, 44 statements were valid to measure commitment, integrity, professional attitude, and hard work. For the reliability, a composite value of reliability >0.70 is used, and the results show that the instrument is reliable.